Durvalumab after definitive chemoradiotherapy in locally advanced unresectable non-small cell lung cancer (NSCLC): real-world data on survival and safety from the German expanded-access program (EAP) - Faehling, Martin; Schumann, Christian; Christopoulos, Petros; Hoffknecht, Petra; Alt, Jürgen; Horn, Marlitt; Eisenmann, Stephan; Schlenska-Lange, Anke; Schütt, Philipp; Steger, Felix; Brückl, Wolfgang M.; Christoph, Daniel C. (Lung cancer, 2020)
checkpoint inhibitor, NSCLC, PD-L1, real world, survival
Gesehen am 04.02.2022